PENGARUH KOMPETENSI, LINGKUNGAN KERJA FISIK DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADAKARYAWAN PT. INDOFOOD CBP SUKSES MAKMUR Tbk SEMARANG) (Students' Journal of Economic and Management, 2014)
This study analyzed the effect of competence, Physical Job environment, and motivation on employee performance. The research object in this paper is PT. Indofood CBP Sukses Makmur Tbk Semarang. Sampling technique in this study is the use of simple random sampling (random) amounted to 90 respondents in the sample by using the method of data collection questionnaire (questionnaire) by distributing a list of questions to respondents in order to obtain information. The purpose of the study was formulated to determine the effect of competence, Physical Job environment and motivation on employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of the instrument, the regression analysis to examine the effect of partially magnitude of each independent variable was tested by regression analysis. The results of the research are:(1).Competence has a positive and significant influence on employee performance. (2). Physical Job environment has a positive and significant impact on employee performance. (3).Motivation has a positive and significant impact on employee performance. Keywords: Competence, Physical Job environment, and Motivation